2012 - Kloser, Harald; Gordon, Mark; Franco, Larry; Emmerich, Roland; Columbia Pictures; Centropolis productio ([Culver City, Calif.] : Columbia Pictures Industries, 2009)
A geophysical team, who are investigating the effect radiation from other solar systems has on the Earth, learn that the core of the Earth is heating up and warn the President of the United States. While the leaders of the world race to build'arks' to escape the impending doom, volcanic eruptions and earthquakes of unprecedented strength wreak havoc all over the world
Title from title screen
Special features: Commentary with writer/director Roland Emmerich and co-writer Harald Kloser; alternate ending; deleted scenes;'Roland Emmerich: the master of the modern epic' featurette; music video'Time for miracles' by Adam Lambert
Director of photography, Dean Semler ; editors, David Brenner, Peter S. Elliott ; music, Harald Kloser, Thomas Wander
Cast: John Cusack, Chiwetel Ejiofor, Amanda Peet, Oliver Platt, Thandie Newton, Danny Glover, Woody Harrelson
DVD format
Dolby digital
Keywords: Two thousand twelve, A.D. -- Drama; Geophysical prediction -- Drama; End of the world (Astronomy) -- Drama; Survivalism -- Drama